2022
DOI: 10.7717/peerj.13009
|View full text |Cite
|
Sign up to set email alerts
|

Water stress and nitrogen supply affect floral traits and pollination of the white mustard,Sinapis alba(Brassicaceae)

Abstract: Changes in environmental conditions are likely to have a complex effect on the growth of plants, their phenology, plant-pollinator interactions, and reproductive success. The current world is facing an ongoing climate change along with other human-induced environmental changes. Most research has focused on the impact of increasing temperature as a major driving force for climate change, but other factors may have important impacts on plant traits and pollination too and these effects may vary from season to se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…reduction in the duration of visits to staminate flowers. Several studies have found that an increase in temperature (0.7 to 4°C), negatively affects the attractiveness of plants to their pollinators due to a decrease in vegetative growth, production and size of flowers, and the production and quality of nectar (Petanidou and Smets, 1996;Saavedra et al, 2003;Sato et al, 2006;Hoover et al, 2012;Liu et al, 2012;Scaven and Rafferty, 2013;Takkis et al, 2015;Mu et al, 2015;Descamps et al, 2018;Descamps et al, 2020;Akter and Klecǩa, 2022). Discrepancies with these studies may be because these have focused on plants from temperate regions (i.e., latitudes greater than 32°), where more drastic temperature changes are expected (Saavedra et al, 2003;Feeley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…reduction in the duration of visits to staminate flowers. Several studies have found that an increase in temperature (0.7 to 4°C), negatively affects the attractiveness of plants to their pollinators due to a decrease in vegetative growth, production and size of flowers, and the production and quality of nectar (Petanidou and Smets, 1996;Saavedra et al, 2003;Sato et al, 2006;Hoover et al, 2012;Liu et al, 2012;Scaven and Rafferty, 2013;Takkis et al, 2015;Mu et al, 2015;Descamps et al, 2018;Descamps et al, 2020;Akter and Klecǩa, 2022). Discrepancies with these studies may be because these have focused on plants from temperate regions (i.e., latitudes greater than 32°), where more drastic temperature changes are expected (Saavedra et al, 2003;Feeley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Even when tropical plants may be less vulnerable to higher temperatures than temperate plants, studies about the response of their interactors (mutualists and antagonists) to these changes are needed to understand whether plant species are prone to persist under climate change scenarios. Moreover, further studies should examine the effects of other main drivers of global change (i.e., nitrogen deposition, increasing atmospheric carbon dioxide, water availability; see Hoover et al, 2012;Akter and Klecǩa, 2022) on main crops to have a better vision of what the future holds in terms of food security.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we present one of the first studies examining the influence and interaction of nitrogen and phosphorus soil nutrients on a plant's floral traits, including reward nutritional quality, and directly testing these effects on pollinator attractiveness and plant fitness 16 , 18 , 19 , 26 . We studied the plant’s complete life cycle and measured the effects of nitrogen and phosphorus nutrient concentrations and ratios ranging from limitation to surplus.…”
Section: Introductionmentioning
confidence: 99%